2020
DOI: 10.1016/j.numecd.2020.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Reducing metabolic syndrome through a community-based lifestyle intervention in African American women

Abstract: Background and Aims-Metabolic syndrome (MetS) increases the risk of cardiovascular disease and type 2 diabetes. Despite a higher prevalence of MetS in African American (AA) women, little is known about the effectiveness of lifestyle interventions in improving metabolic markers in this high-risk group. This study investigated the effectiveness of a community-based lifestyle intervention delivered by lay health coaches in reducing MetS among AA women.Methods and Results-A cluster-randomized diabetes prevention p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…A systemic, practical and low-cost approach to treating MetS is needed, but there still seems to be an absence of systemic solutions focused on the needs of older women with metabolic conditions and depressive symptoms [ 87 ]. Results of this study indicate the validity of conducting a multimodal therapeutic approach in rehabilitation combining physical activity with health-related psychoeducation, which is consistent with other studies focusing on lifestyle changes in the treatment of MetS in women [ 88 , 89 , 90 , 91 , 92 ].…”
Section: Discussionsupporting
confidence: 89%
“…A systemic, practical and low-cost approach to treating MetS is needed, but there still seems to be an absence of systemic solutions focused on the needs of older women with metabolic conditions and depressive symptoms [ 87 ]. Results of this study indicate the validity of conducting a multimodal therapeutic approach in rehabilitation combining physical activity with health-related psychoeducation, which is consistent with other studies focusing on lifestyle changes in the treatment of MetS in women [ 88 , 89 , 90 , 91 , 92 ].…”
Section: Discussionsupporting
confidence: 89%
“… 44 MetS has also been reported to increase the risk of T2DM. 45 Therefore, we had added a sensitivity analysis excluding CVD (including myocardial infarction, coronary heart disease, and hypertension) and T2DM to minimize the potential confounding effects.…”
Section: Methodsmentioning
confidence: 99%
“…MetS is an independent predictor of CVD, and the prevalence for CVD increased with increasing number of MetS components 44 . MetS has also been reported to increase the risk of T2DM 45 . Therefore, we had added a sensitivity analysis excluding CVD (including myocardial infarction, coronary heart disease, and hypertension) and T2DM to minimize the potential confounding effects.…”
Section: Methodsmentioning
confidence: 99%
“…Church partnerships incorporating Bible study and small group-based nutrition education provided by pastors and church members also increased vegetable uptake [ 49 ]. Faith-based dietary coaching to reduce calories, fat, and salt were also effective [ 50 ]. One study showed that church-based interventions could have long-lasting effects, up to 24 months [ 51 ].…”
Section: Methodsmentioning
confidence: 99%